Temperature-Dependent Alkyl Glycerol Ether Lipid Composition of Mesophilic and Thermophilic Sulfate-Reducing Bacteria - Vinçon-Laugier, Arnauld; Cravo-Laureau, Cristiana; Mitteau, Isabelle; Grossi, Vincent (Frontiers in Microbiology, 2017)
The occurrence of non-isoprenoid alkyl glycerol ether lipids in Bacteria and natural environments is increasingly being reported and the specificity and diagenetic stability of these lipids make them powerful biomarkers for biogeochemical and environmental studies. Yet the environmental controls on the biosynthesis of these peculiar membrane lipids remain poorly documented. Here, the lipid composition of two mesophilic (Desulfatibacillum aliphaticivorans and D. alkenivorans) and one thermophilic (Thermodesulfobacterium commune) sulfate reducing bacteria - whose membranes are mostly composed of ether lipids - was investigated as a function of growth temperature (20-40°C and 54-84°C, respectively). For all strains, the cellular lipid content (relative to proteins) was lower at sub- or supra-optimal growth temperature, but the relative proportions of dialkyl glycerols, monoalkyl glycerols and fatty acids remained remarkably stable whatever the growth temperature. Rather than changing the proportions of the different lipid classes, the three strains responded to temperature changes by modifying the average structural composition of the alkyl and acyl chains constitutive of their membrane lipids. Major adaptive mechanisms concerned modifications of the level of branching and of the proportions of the different methyl branched lipids. Specifically, an increase in temperature induced mesophilic strains to produce less dimethyl branched dialkyl glycerols and 10-methyl branched lipids relative to linear structures, and the thermophilic strain to decrease the proportion of anteiso relative to iso methyl branched compounds. These modifications were in agreement with a regulation of the membrane fluidity. In one mesophilic and the thermophilic strains, a modification of the growth temperature further induced changes in the relative proportions of sn-1 vs sn-2 monoalkyl glycerols, suggesting an unprecedented mechanism of homeoviscous adaptation in Bacteria. Strong linear correlations observed between different ratios of alkyl glycerols and temperature allow to hypothesize the use of these specific lipids as indicators of temperature changes in the environment.